2023
DOI: 10.4103/aian.aian_974_22
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barre Syndrome Followed by Covid-19 Infection, Vaccination and Other Precipitating Factors during the Pandemic

Vesna Martic,
Esmer Fejzic,
Milos Danilovic
et al.

Abstract: Background and Aims: Guillain-Barré syndrome (GBS) is usually triggered by an infection. Vaccination is mentioned as a possible trigger in a small number of GBS cases. The aim of this study was to notice GBS distinctness provoked by various triggers during the COVID-19 pandemic. Material and Methods: A total of 109 GBS patients were divided into three groups, respectively: COVID-19 infection associated (19 patients), COVID-19 vaccination associated (16 patients) and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As seen in multiple other studies and articles, the best therapeutic for GBS related to COVID-19 is the standard IVIg therapy and plasma exchange treatment. The difference between regular treatment before and after being affected by COVID-19 was not drastic, and patients should continue to follow the standard therapeutics of any GBS patient [ 134 ]. GBS, being an inflammatory polyradiculoneuropathy, is associated with numerous viral infections.…”
Section: Reviewmentioning
confidence: 99%
“…As seen in multiple other studies and articles, the best therapeutic for GBS related to COVID-19 is the standard IVIg therapy and plasma exchange treatment. The difference between regular treatment before and after being affected by COVID-19 was not drastic, and patients should continue to follow the standard therapeutics of any GBS patient [ 134 ]. GBS, being an inflammatory polyradiculoneuropathy, is associated with numerous viral infections.…”
Section: Reviewmentioning
confidence: 99%
“…have presented an original study on the GBS followed by coronavirus disease 2019 (COVID-19) infection, vaccination, and other precipitating factors during the pandemic in Serbia and Montenegro. [ 2 ] They retrospectively recruited 109 GBS patients between January and April 2022 into the following three groups: COVID-19 infection-associated (19 cases), COVID-19 vaccination-associated (16 cases), and other causes (74 cases). Individuals positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on polymerase chain reaction (PCR) testing were classified as COVID-19-positive.…”
mentioning
confidence: 99%
“…The authors reported 16 cases of COVID-19 vaccine-induced GBS in the background of 54.1% coverage in adults in a population of 7,806,891 people. [ 2 ] The first dose of vaccines was the most common dose implicated, with Sinopharm use associated with most cases. AstraZeneca and Covaxin were the vaccines most commonly used in India, and very few vaccine-associated GBS cases have been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation